Design of Behavioral Counseling Model with Self Management Technique in Improving Student Discipline (Study of Class VIII SMP Negeri 5 Kota Solok) - Syafnita, Putri; Nita, Rahma Wira; Suryadi, Suryadi (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This research was motivated by the existence of students who had low discipline while in the school environment. This research aims to find out: 1) Describe an overview of the disciplinary conditions of students using self-management techniques at SMPN 5 Kota Solok. 2) Designing a behavioral counseling model with self-management techniques to help develop student discipline. This research uses Research and Development (R&D) research. The population of this study was class VIII students with a total of 220 students. The number of samples in this study was 32 students. The sampling technique in this research used purposive sampling, and the instrument used was a questionnaire.